Parasitic Disease Screening among HIV Patients from Endemic Countries in a Toronto Clinic - Cecilia T Costiniuk; Curtis L Cooper; Steve Doucette; Colin M Kovacs (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Many North American-based HIV patients originate from parasitic disease-endemic regions. Strongyloidiasis, schistosomiasis and filariasis are important due to their wide distribution and potential for severe morbidity.